Optimal Portfolio Construction using Single Index Model: A Comparative Study of Largest Market Capitalization and Most Active Trading Volume Stocks - Mulya, Yudhia; ., Herdiyana (International Journal of Engineering and Technology, 2018)
The increasing growth of Jakarta stock index enhanced by increasing trends in trading volume and market capitalization. This study aimed to construct portfolio of largest market capitalization portfolio and most-active trading volume portfolio with 1 year and 6-months holding period and compare the return and risk performance of each portfolios. Single index model was conducted to construct the optimum portfolio by using daily return of stocks listed in Jakarta Stock Exchange during the year of 2016.The result showed that the most active trading volume portfolio comprised more stocks than the largest market capitalization portfolio. The optimal portfolios also showed that each group of stocks has different sector orientation in terms of sector weights. Property and real estate sector has the maximum proportion of the largest market capitalization portfolio, while mining sector has the maximum proportion in the most-active trading volume optimum portfolio. The 6-months formation period of portfolio period showed that most active stocks portfolios has higher cumulative return that the largest market capitalization portfolios inwhich both portfolios has higher cumulative return than the Jakarta Composite Index return. Largest market capitalization portfolio was better performed in 6-months formation period, while most active trading volume portfolio in one-year period.Â Â